Industrialization of Election Infringement in Simultaneous Elections: Lessons from Sweden - Putra Perbawa, Ketut Sukewati Lanang; Hanum, Willy Naresta; Atabekov , Almaz Karimovich (Lembaga Contrarius Indonesia, 2024)
Election violations are increasingly occurring on a massive scale. In Indonesia, by early 2024, 1,032 violations had been handled only for the simultaneous general elections for president, vice president, and members of national and regional legislatures. Meanwhile, the results of handling violations in the 2019 simultaneous elections increased sharply to 21,169 cases, or an increase of 58.3% from 2014. This was due to the material on Indonesia's general election regulations, which overlapped and were not in harmony with the Constitution and judges' decisions. This research aims to analyze the issues surrounding simultaneous general elections in Indonesia and outline alternative progressive policies for achieving democratic governance with dignity and integrity during the next general election. This research focuses on normative law, utilizing statutory and conceptual approaches that pertain to democracy, elections, and various types of violations. To get an overview of the new policy, this research compares the handling of election violations in Indonesia with that in Sweden. The research results show violations of the general election administration, the code of ethics for election organizers, election crimes, and other legal violations in Indonesia and Sweden. However, Sweden still maintains its democratic stability. Several election manipulation factors that become fraud or violations are the manipulation of election rules, the manipulation of vote conditioning in the form of money politics, the updating of voter lists, and the conditioning of candidate requirements to cyberattacks. Therefore, it is crucial for regulations, participants, and the voting public to reevaluate the integrity of elections.